(3efGbH GdCHQGQ heMGSf GdCNjGQs - (3GdMSjf Hf fUQ, ef Hfj NejS GdcYHqj GdehUdqj GdLgfqj , GpHf nNpejS,J (B552 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj CcQe YHGOg HGdYfGjI s
(3ofSNI ocJHJ SfI (B573 (3g`s
(3HQSe NRGfI GdGejf GdCLd GdSjO GdcHjQ CHj GdeXaQs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B261 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B66s
Keywords: (3GdJGQjNs